Sources of science-related information and trust in these sources in the light of the results of the survey conducted as part of the public consultations in the framework of the CONCISE project - Podgórniak-Krzykacz, Aldona; Wiktorowicz, Justyna (Science Communication in Poland. Participation. Dialogue. Trust, 2021)
The chapter presents the results of a survey carried out among the participants of public consultations conducted in the framework of the CONCISE project (n = 100). It focused on issues related to the sources of scientific information on the four topics under consideration ‒ climate change, alternative and non-conventional medicine, vaccines, and genetically modified food. The analysis covered the frequency of use and trust in sources of information such as the Ministry of Health, the European Union, international organisations, non-governmental organisations, private companies, opinion leaders, as well as family and friends. The use of media in this area was also assessed – both traditional and electronic. The study indicated the importance of friends and family as a source of knowledge. In the case of alternative medicine, climate change and vaccines, non-governmental organisations were also important, and in the case of GMOs – the European Union. However, international organisations (e.g. the UN, WHO) were named the most reliable source of scientific information on all four topics. When it comes to the media, information on scientific topics most often reaches Poles from multi-thematic and monothematic websites, as well as via Facebook. TV programmes and popular science magazines were also mentioned with a similar frequency. The popularity of individual electronic and traditional media is primarily related to age, and in the case of some channels, also to the level of education and/or place of residence.